Creating teaching and learning materials for kadazandusun as a less commonly taught language based on elements of learning style preferences of kadazandusun learners in UMS - Veronica P. Atin; Rosy Talin (Pusat Penataran Ilmu Bahasa, Universiti Malaysia Sabah, 2020)
In University Malaysia Sabah (UMS), Kadazandusun (KD) is offered as a foreign language (or third language) to Malaysian learners of other ethnic groups. As KD is a less commonly taught language, it is still in the process of “developing”, including in the aspect of teaching and learning materials. In this paper, we present the results of a quantitative survey of learning styles of 132 learners of Kadazandusun as a foreign language in UMS. From the findings, we suggests ways to include the elements of the learners’ preferred LS to create KD teaching and learning materials. In conducting the study, the Learning Style Survey (LLS) developed by Cohen, Oxford and Chi (2002) was utilized. Three domains of LSS: perceptual, psychological, and cognitive learning styles are included in the questionnaire which are elicited using 110 items. SPSS version 26 was used to analyse the completed questionnaire. It was revealed that in the area of Sensory Learning, a majority of the learners are visually oriented. In the three areas of psychological learning style, the preferences are introverted, random intuitive and closure-oriented. Whereas in the seven aspects of cognitive learning style assessed, the preferences are particular, analytical, sharpener, deductive, field independent, reflective and metaphoric. Based on the dominant preferences of LS, we propose how the elements can be used to create teaching and learning materials for KD.